Nursing Educators’ and Students’ Perspectives Regarding Online Learning During the Pandemic in Saudi Arabia - Castro GMT; Taala WD; Guerrero JG; Rosales NS; De Sagun RS; Cordero RP; Ciriaco RN; Javines RG (Dove Medical Press, 2022)
Grace Medalyn T Castro,1 William D Taala,1 Jefferson G Guerrero,1 Niela S Rosales,1 Rino S De Sagun,2 Rock P Cordero,3 Rolven N Ciriaco,4 Rayson G Javines4 1Nursing Department, Fakeeh College for Medical Sciences, Jeddah, Saudi Arabia; 2College of Nursing, University of Hail, Hail, Saudi Arabia; 3Nursing Department, University of Fujairah, Fujairah, United Arab Emirates; 4College of Nursing, University San Agustin, Iloilo, PhilippinesCorrespondence: William D Taala, Nursing Department, Fakeeh College for Medical Sciences, P.O. Box 2537, Jeddah, 21461, Saudi Arabia, Tel +966 532543021, Email wtaala@fcms.edu.saPurpose: The study aimed to determine nursing educators' and students' perspectives concerning the shift of teaching methodologies to online learning platform in nursing education during the COVID-19 pandemic.Materials and Methods: The cross-sectional study investigated nursing educators' and students' perspectives on online learning. Non-probability convenience sampling technique was used to recruit 120 educators and 350 students, who answered the Test of e-Learning Related Attitudes scale. The data collection was conducted from November to December 2020 in five selected colleges and universities in Saudi Arabia.Results: The findings of the study revealed that the overall mean score of the nursing educators' perspectives on online learning based on the 4 dimensions were 4.18 with a SD of 0.57 and an overall mean score of 4.22 with a SD of 0.61 for the students. Furthermore, the perspectives of both participant groups on challenges and benefits dimensions shows that there was significant difference as supported by a p-value of < 0.001 and 0.046. However, it shows in the attitude and interest dimensions that there was no significant difference as supported by a p-value of 0.313 and 0.088, respectively.Conclusion: Nursing educators and students shows an agreement on their perspectives on online learning in terms of attitude and interest dimensions. However, they show their disagreement in terms of challenges and benefits dimensions. Unfortunately, the current COVID-19 pandemic situation could persist for several years. But modern technologies can partially solve current problems in nursing education.Keywords: COVID-19, nursing education, online learning, teaching and learning, methodologies